Suicide in French Polynesia: a retrospective analysis based on medicolegal documents and interview with family. Issue 9 (September 2021) - Amadéo, Stephane; Rereao, Moerani; Vanquin David, Germaine; Nguyen, NgocLam; Séguin, Monique; Beauchamp, Guy; Favro, Patrick; Trouche, Heimana; Malogne, Aurélia; Goodfellow, Benjamin; Gokalsing, Erick; Spodenkiewicz, Michel; et al.
Objective: To analyse the epidemiological data on suicide in French Polynesia (FP). Methods: Data on suicides were collected from the Public Health Direction, Judicial Police Investigations Court of Justice records, the Centre d'Opérations et de Renseignements de la Gendarmerie, patient records for those hospitalized in psychiatry and from psychological autopsies. Results: The dataset consisted of 316 suicide cases in FP over 25 years (1992–2016). In FP, suicide was more frequent in men (sex ratio 3.2:1), young people (mean age, 34.4 years) and individuals with previously diagnosed psychiatric disorders (100 of 316; 31.6%) The most common method of suicide was hanging (276 of 316; 87.3%). A history of previous suicide attempts was found in 25 of 56 (44.6%) of suicide cases, when documented. The most common potential triggering factors for suicide were emotional problems. The suicide rates have remained stable during 1992–2016 (mean 10.6/100 000 inhabitants per year), with periods of economic crises increasing suicide rates. Conclusions: These results provide valuable information to enable the effective targeting of suicide prevention strategies toward those at high risk. Economic crises had larger impacts in the French overseas territories than mainland France. Given the unprecedented economic impact of the Covid-19 pandemic in FP, there is an urgent need to implement suicide epidemiological surveillance and prevention programmes.